Development of canva-based mathematics E-Comics on equivalent fraction material for grade IV elementary school students - Saputro, Hengkang Bara; Arima, Yuni (International Journal of Progressive Mathematics Education, 2024)
Purpose: This study aims to describe the development procedures and evaluate the quality and feasibility of a mathematics e-comic using a habitual approach to align learning with students' daily routines. Design/methodology/approach: This research follows the Research and Development (R&D) methodology employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included media, content, instructional, and language experts, alongside classroom teachers and students for pilot testing. Findings: The e-comic was deemed highly feasible based on validation from media (90), content (90), and language (92) experts in the "Excellent" category, and instructional experts (80) in the "Good" category. Practical assessment by teachers scored 91 (Excellent), while student responses reached 84 (Good), confirming the product's quality for classroom use.Practical implications: This e-comic serves as a practical solution for educators to provide comprehensive, engaging, and relevant mathematics instructional media that resonates with students' digital preferences. Originality/value: This study innovatively integrates a habitual approach within a digital comic format, contributing a unique instructional design that bridges abstract mathematical concepts with students' everyday habits.   Purpose: Penelitian ini bertujuan untuk mendeskripsikan prosedur pengembangan dan mengevaluasi kualitas serta kelayakan e-komik matematika berbasis pendekatan kebiasaan (habitual approach) guna menciptakan pembelajaran yang relevan dengan keseharian siswa. Design/methodology/approach: Menggunakan metode Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian melibatkan ahli media, materi, pembelajaran, bahasa, serta guru kelas dan peserta didik sebagai responden uji coba. Findings: Produk dinyatakan sangat berkualitas dan layak melalui validasi ahli media (90), materi (90), dan bahasa (92) dengan kriteria "Sangat Baik", serta ahli pembelajaran (80) berkriteria "Baik". Uji praktis oleh guru kelas mencapai skor 91 (Sangat Baik) dan respon peserta didik sebesar 84 (Baik), menunjukkan efektivitas produk dalam pembelajaran. Practical implications: E-komik ini memberikan solusi praktis bagi pendidik dalam menghadirkan media pembelajaran matematika yang komprehensif, menarik, dan selaras dengan karakteristik digital peserta didik. Originality/value: Studi ini mengintegrasikan pendekatan kebiasaan ke dalam format komik digital, menawarkan kebaruan dalam desain instruksional matematika yang menjembatani konten abstrak dengan rutinitas siswa.